2013
DOI: 10.1111/josh.12102
|View full text |Cite
|
Sign up to set email alerts
|

School Nurses' Role in Asthma Management, School Absenteeism, and Cost Savings: A Demonstration Project

Abstract: Full-time school nurses play an important role in improving asthma management among students in underserved schools, which can impact school absenteeism and attendance-related economic costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 20 publications
0
69
0
1
Order By: Relevance
“…Then, we assess teachers’ perceptions on the impact of having school nurses providing follow-up and appropriate treatment. Other results of the overall nurse demonstration project have been reported elsewhere [28,29]. …”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Then, we assess teachers’ perceptions on the impact of having school nurses providing follow-up and appropriate treatment. Other results of the overall nurse demonstration project have been reported elsewhere [28,29]. …”
Section: Methodsmentioning
confidence: 97%
“…All the nurses were equally trained to perform vision and hearing screenings and customary follow-up, but only full-time nurses in demonstration schools were able to provide comprehensive follow-ups and care coordination with other health care providers [28]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peterson-Sweeney et al (2007) found that asthma education from the child's health care provider positively influenced parental belief systems, particularly attitudes toward anti-inflammatory medications and facts about asthma. Rodriguez et al (2013) found that schools with full-time nurses had less school absenteeism for asthma and less emergency room utilization than schools with parttime nurse, resulting in substantial cost savings to both the school districts and the families. Engelke, Swanson, and Guttu (2014) found that school nurse case management for students with asthma resulted in decreased emergency room visits, increased academic performance, reduced episodes of respiratory distress, and improved peak flow rates.…”
Section: Perceived Susceptibilitymentioning
confidence: 97%
“…School nurse involvement in asthma care coordination has resulted in improvements in health care use, school attendance, medication adherence, and quality of life. 3,4,6,7 School nurses are uniquely positioned to provide direct care, adherence counseling, and education for asthmatic patients. 8 They can review and reinforce proper inhaler technique and usually have the most recorded data of quick-relief medication use—one of the hallmarks of asthma control.…”
Section: Componentmentioning
confidence: 99%